Zwitterionic copolymer modified polyethersulphone/sulfonated polysulphone membranes for enhancing dye/salt selective separation. Issue 21 (24th October 2021) - Liu, Gansheng; Tao, Ran; Hu, Mengyang; Liu, Xiaowei; Matindi, Christine; Kadanyo, Sania; Chen, Rui; Mao, Liuyong; Fang, Kuanjun; Li, Jianxin
Abstract: Two monomers, positively charged N, N‐dimethylaminoethyl methacrylate (DMAEMA) and negatively charged monomer sodium vinylsulfonate (VSA), were employed to generate a zwitterionic copolymer layer on the surface of PES/SPSf blend membrane via UV‐light grafting. The effect of monomer concentration and irradiation time on the properties of the modified membranes was studied. Results showed that the degree of grafting (DG) accelerated with the increase in monomer concentration and irradiation time. The zeta potential of the zwitterionic membrane was tailored from negative (−21.4 mV) to positive charge (+30.8 mV) by varying the concentration DMAEMA monomer and irradiation time. Optimized membrane fabrication conditions were 15 g L −1 of DMAEMA and 10 min irradiation time (Mc15). The molecular weight cut‐off of Mc15 was calculated to be 40 kDa, while the zeta potential was found to be +8.56 mV (pH = 7). Mc15 showed excellent rejection rates for both positively and negatively charged dyes. In contrast Mc15 maintained low rejection rates for Na2 SO4 (<10%) and high dye/salt selective separation performance (retention rates for basic blue 26 and Na2 SO4 were 97 and 6.5%) over long continuous operation (50 h). In summary, our study provides tailoring implementation strategies to enhance dye/salt selective separation of tight ultrafiltration membranes. Abstract :